Diagnostics and Treatment of Traumatic Damages to Achilles Tendon - Skiba, K. (Engineering Transactions, 2003)
Traumatic damages of Achilles tendon constitute an important and serious problem in clinical practice. Many theories are applied in order to explain the pathomechanism of traumatic damages of Achilles tendon. Among them, there is a mechanical theory which claims that sudden and not co-ordinated contraction of the calf triceps muscle with plantarly bent foot and extended limb causes rupture of the tendon continuity. In clinical practice, Achilles tendon appeared more susceptible to rupture in persons over 35 when elasticity degree is reduced due to the tendon deformative lesions (fragmentation and collagen fibres homogenisation). In the Department of Traumatic Surgery and Hand Surgery of the Wrocław University of Medicine, since 1993, clinical surveys have been carried on upgrading the surgical treatment methods of traumatic and subcutaneous ruptures of the Achilles tendon. In years 1995–1999, the examinations were carried on in cooperation with the Institute of Material Science and Applied Mechanics, Wrocław University of Technology in order to explain the pathomechanism of traumatic lesions of Achilles tendon. New examination methods such as: ultrasonography, tomography, magnetic resonance as well as recent thermo-vision method contribute largely towards evaluation of both early and long-term results of operative treatment.